Correlation of Ferritin Level to The Quality of Life - Ariyanto Nugroho; Iri Kuswadi; Bambang Djarwoto (Faculty of Medicine Universitas Gadjah Mada, 2014)
ABSTRACTBackground: Chronic kidney disease is a worldwide health problem. Circumstances that caused the condition of end-stage renal failure causes a decrease in quality of life with a high mortality rate ranging from 22% per year. Many ways to assess the quality of life, form-36 (SF-36) has undergone several revisions refi nement. Serum ferritin continues to be the focus of attention. Nearly half of all hemodialysis patients had serum ferritin > 500 ng/ml. Serum ferritin is a marker of infl ammation that is a good, low levels correlated with iron defi ciency and high levels correlated with infl ammation.Objective: To determine the correlation of high levels of serum ferritin to decline in the quality of life in patients with CRF who had been undergoing hemodialysisMethods: This study was a cross sectional study to determine whether high levels of serum ferritin may have an impact on the decline in the quality of life in patients with chronic renal failure (CRF) who had undergone regular hemodialysis. The study was conducted at Hospital Hemodialysis Unit Dr. Sardjito,Yogyakarta. Result: A total of 61 patients who met the inclusion criteria to undergo research. Score KDQOL-SF in this study, negative correlations (weak) significant in sleep (sleep disorders) 58.79 ± 1.95 (r = -0.306) and (p = 0.017). On the Role Physical scores (physical activity) 24.59 ± 3.21 obtained a negative correlation (weak) signifi cant (r = -0.268) and (p = 0.037). For Emotional Well Being scores (emotional condition) 70.85 ± 1.39 (r = -0.374) and (p = 0.003). On the score of Energy Fatigue (physical fatigue) 62.29 ± 1.61 (r = -0.261) and (p = 0.043).Conclusion: Overall, this study shows the lack of statistically signifi cant results showed a high correlation ferritin directly on quality of life.Keywords: chronic renal failure, hemodialysis, ferritin, KDQOL-SF